2021
DOI: 10.1186/s13567-021-00974-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular biomarkers associated with disease progression in the testis of bulls infected with Besnoitia besnoiti

Abstract: Breeding bulls infected with Besnoitia besnoiti may develop sterility during either acute or chronic infection. The aim of this study was to investigate the molecular pathogenesis of B. besnoiti infection with prognosis value in bull sterility. Accordingly, five well-characterized groups of naturally and experimentally infected males were selected for the study based on clinical signs and lesions compatible with B. besnoiti infection, serological results and parasite detection. A broad panel of molecular marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Another limitation was the small sample size (only three acutely infected bulls with testicular degeneration were evaluated), which may have also contributed to the fact that no markers of sterility were identified. Nevertheless, this study offers robust data and complements a previous study that identified a few molecular markers related to disease progression in testicular tissues [ 13 ]. Moreover, the results obtained in experimentally infected cattle offer valuable data about the kinetics of the acute-phase response during acute and chronic infection, as discussed below.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Another limitation was the small sample size (only three acutely infected bulls with testicular degeneration were evaluated), which may have also contributed to the fact that no markers of sterility were identified. Nevertheless, this study offers robust data and complements a previous study that identified a few molecular markers related to disease progression in testicular tissues [ 13 ]. Moreover, the results obtained in experimentally infected cattle offer valuable data about the kinetics of the acute-phase response during acute and chronic infection, as discussed below.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, animals with chronic infection, in addition to having values of 70 g/l (Fig. 2 ), also presented an intense inflammatory infiltrate with the presence of lymphocytes, some macrophages, abundant young granulation tissue and an abundance of fibroblasts in the testicular parenchyma [ 13 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 Sterility (aspermatogenesis) in males may occur during both the acute and chronic phase of infection, and be caused by necrotising orchitis leading to atrophy and induration of the testes. 27,28 Tissue cysts in the scleral (bulbar) conjunctiva are clinically pathognomonic and develop 6-7 weeks after infection. 1,2,6,11 In endemic situations, cattle mortality rates of <1% are expected.…”
Section: Introductionmentioning
confidence: 99%